Identification of Rab18 as an Essential Host Factor for BK Polyomavirus Infection Using a Whole-Genome RNA Interference Screen - Linbo Zhao (American Society for Microbiology, 2017)
ABSTRACT BK polyomavirus (BKPyV) is a human pathogen first isolated in 1971. BKPyV infection is ubiquitous in the human population, with over 80% of adults worldwide being seropositive for BKPyV. BKPyV infection is usually asymptomatic; however, BKPyV reactivation in immunosuppressed transplant patients causes two diseases, polyomavirus-associated nephropathy and hemorrhagic cystitis. To establish a successful infection in host cells, BKPyV must travel in retrograde transport vesicles to reach the nucleus. To make this happen, BKPyV requires the cooperation of host cell proteins. To further identify host factors associated with BKPyV entry and intracellular trafficking, we performed a whole-genome small interfering RNA screen on BKPyV infection of primary human renal proximal tubule epithelial cells. The results revealed the importance of Ras-related protein Rab18 and syntaxin 18 for BKPyV infection. Our subsequent experiments implicated additional factors that interact with this pathway and suggest a more detailed model of the intracellular trafficking process, indicating that BKPyV reaches the endoplasmic reticulum (ER) lumen through a retrograde transport pathway between the late endosome and the ER. IMPORTANCE Polyomaviruses bind to a group of specific gangliosides on the plasma membrane of the cell prior to being endocytosed. They then follow a retrograde trafficking pathway to reach the endoplasmic reticulum (ER). The viruses begin to disassemble in the ER and then exit the ER and move to the nucleus. However, the details of intracellular trafficking between the endosome and the ER are largely unknown. By implementing a whole human genome small interfering RNA screen, we identified Rab18, syntaxin 18, and the NRZ complex as key components in endosome-ER trafficking of the human polyomavirus BKPyV. These results serve to further elucidate the route BKPyV takes from outside the cell to its site of replication in the nucleus.